2018
DOI: 10.3390/publications6010002
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Notices: Who Authored Them?

Abstract: Unlike other academic publications whose authorship is eagerly claimed, the provenance of retraction notices (RNs) is often obscured presumably because the retraction of published research is associated with undesirable behavior and consequently carries negative consequences for the individuals involved. The ambiguity of authorship, however, has serious ethical ramifications and creates methodological problems for research on RNs that requires clear authorship attribution. This article reports a study conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 98 publications
(82 reference statements)
1
8
0
Order By: Relevance
“…Hence, the apology and the responsibility cannot be attributed to a specific actor. This tendency of apologies to blur the actual speakers mirrors the tendency of retractions to cloud their own authorship (Hu & Xu, 2018), which is also very prominent in the present sample.…”
Section: Social Ambivalencesupporting
confidence: 60%
See 2 more Smart Citations
“…Hence, the apology and the responsibility cannot be attributed to a specific actor. This tendency of apologies to blur the actual speakers mirrors the tendency of retractions to cloud their own authorship (Hu & Xu, 2018), which is also very prominent in the present sample.…”
Section: Social Ambivalencesupporting
confidence: 60%
“…All results were manually checked for false positives, before drawing a random sample stratified by period for JSTOR (1980-1989, 1990-1999, 2000-2014), and for WOS (1990-1999 and 2000-2014), while all notices identified in EconBiz were used. 2 Being a relatively new format, retraction notices have received little attention from a discourse analytical perspective (but see Hu & Xu, 2018). To provide an overview of the characteristics of this emerging textual format, we employed a genre-based perspective on English for Academic Purposes as a "workable way to make sense of the myriad communicative events that occur in the contemporary English-speaking academy" (Swales, 1990, p. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening and detection by peers and editors was unable to prevent this paper with false elements from being published, so editors should be held accountable to some extent ( 16 ), although editorial oversight resulting from deception by false authors should be forgiven without attaching a stigma to it ( 17 ). The relative opacity of the retraction notice is another problem ( 18 ).…”
mentioning
confidence: 99%
“…. has serious ethical ramifications and creates methodological problems for research on RNs that requires clear authorship attribution" [4]. Their study identified some RN textual features that could be used "to disambiguate obscured authorship".…”
mentioning
confidence: 99%